(untitled) (Al-Academy, 2023)
Each era has advantages in terms of innovation and development in form, technology, style, and design in ceramic vessels, both at the level of functional and aesthetic performance, so this study aimed to demonstrate the importance of geometrical foundations in the design structure of contemporary ceramic vessels, and also to reveal the constructive skills in The structure of the ceramic figure.The researchers used the descriptive analytical approach to suit the nature of the study, and they described and analyzed the ceramic works in terms of geometric shape systems, elements and foundations of design in construction, formal diversity in the general design of ceramic vessels, and references and sources of artwork. In addition to the above, the researchers reached a set of results one of the important:The diversity in the structural design of the geometric form confirmed the distance from inertia by emphasizing the linear and expressive values, which contributed to the enrichment of the ceramic vessels. And the interest in monochrome in the geometric design of the earthenware, which enhanced the formal expression and unity in the structural design. The emphasis is on two-part geometric shapes, emphasizing mass and emptiness, and the balance between interior and exterior spaces. And also the distance from the traditional style, through geometrical modification and formation, and the creation of contemporary ceramic shapes through the plurality of ceramic pieces in one structural composition and their translation in the language of shapes in the final achievement of contemporary ceramic vessels, And focus on the phenomenon of structural reflection in the contemporary design of the form